KEADAAN DIMORFISME SEKSUAL SECARA MORFOMETRI DAN PERBEDAN INTRASPESIFIK RELUNG PAKAN PADA KADAL Mabuya multifsciata (LACERTILIA: SCINCIDAE) - Hellen Kurniati; Agus H. Tjakrawidjaja; Gono Semiadi (The East Java Biological Society, 1997)
Differences on body size between male and female scincids generally influence intraspecific food niche. However information on the sexual dimorphism on M. multifasciata is unavailable. The aim of this study was to understand the relation between sexual dimorphism on the body size and food niche difference. Fifty four specimen of M. multifasciata consisted of 19 adult males, 23 adult females, and 12 subadult were collected from Indonesian Botanical Garden in Bali and they were measured for their morphology. The result on univariant, correlation and multiple regression statistical analyses on morphology of variant snout to vent length (SVL), mount length (ML), mount wide (MW), humerus length (HL), radius length (RL), femur length (FL), and tibia length (TL) on adult males, adult females and subadult of M. multifasciata revealed that there were no sexual dimorphism between adult males and adult females; strong correlation among the varians, and regression square of all the variants to SVL on adult males, adult females, and subadult up to 0.96. the intraspecific food niche differences between adult males and adult females had no effect on the sexual dimorphism.